Analisis Ketebalan Bawah Permukaan Endapan Mineral Grafit Alam di Kelurahan Watuliandu, Kecamatan Kolaka, Kabupaten Kolaka - Asfar, Suryawan; Okto, Ali; Jahidin, Jahidin; Alfirman, Alfirman; Jurzan, La Ode Ihksan; Hadiyanto, Yoko (Jurnal Geomine, 2020)
The graphite mineral resource is one of the minerals contained in the region of Southeast Sulawesi Province. The research activity was undertaken in Watuliandu Village area, District Kolaka Kolaka, Southeast Sulawesi Province. The purpose of this study is to determine the depth and thickness of the subsurface mineral deposits natural graphite, so as to achieve the goal researchers used survey method by utilizing the techniques of observation and data collection directly in the field in the form of measurements of geoelectric resistivity configuration using Schlumberger with the number of passes the measurement of 3 ( three) path and the path length reaches 200 meters and the track surface elevation measurements ranging from 12-56 meters above sea level. Based on the results of measurement and data analysis showed that the type of subsurface lithology encountered rock consists of compact schist, gneiss, schist and graphite, in which each lithology encountered rocks have resistivity values that vary where to compact schist layers ranging from 1,065.65 to 2,065.28 Ωm, gneiss rock layers around 5,506.71 Ωm and graphite schist rock layers ranges from 83.26 to 468.50 Ωm. Based on the analysis of resistivity in mind that natural graphite mineral deposits found in the layers of graphite schist, which is predominantly found on the track 2 with a layer depth ranges from 0 - 35 meters, as well as sediment thickness to ± 35 meters.